THE ROLE OF THE PIRLS INTERNATIONAL ASSESSMENT PROGRAM IN OUR COUNTRY’S EDUCATION SYSTEM: ENHANCING STUDENTS’ READING LITERACY - Karimova Muqaddas (Web of Journals Publishing, 2026)
This article highlights the significance of the PIRLS international assessment program in our country’s education system and its role in identifying and developing reading literacy among primary school students. Through the PIRLS program, opportunities are created to assess and enhance students’ competencies such as text comprehension, analysis, and evaluation.
Keywords: PIRLS, international assessment program, reading literacy, creative thinking, primary education, text analysis, reading culture, conscious reading, creative thinking.